Sampler collection gadget for epilithic diatoms - Salomoni,SE. (2007)
This work present a new gadget for sampling epilithic diatoms from both lentic and lotic enviroments. The sampler consists of a polystyrene cylinder, left to float on the surface of the water, to which stone substrates are attached. This epilithic diatom sampler (EDS) can be used to detect spatial and temporal richness and density variation in the study of the diatom community, as well as in water quality monitoring.